2013
DOI: 10.1016/j.theriogenology.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a GnRH analogue (Maprelin) on the reproductive performance of gilts and sows

Abstract: a b s t r a c tThe ability of peforelin (l-GnRH-III) to stimulate follicular growth, FSH release, and estrus in gilts after altrenogest treatment and in sows after weaning was investigated. In three farrow-to-wean herds, with at least 600 sows and average production performance, 216 gilts, 335 primiparous, and 1299 pluriparous sows were randomly allocated to three treatments: peforelin (M group: Maprelin), eCG (F group: Folligon), and physiological saline solution (C group). Animals were treated 48 hours after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…However, a previous study [9] performed in farms with more average reproductive results (approx. 26 piglets/sow/year) also showed significant effects on estrus rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a previous study [9] performed in farms with more average reproductive results (approx. 26 piglets/sow/year) also showed significant effects on estrus rate.…”
Section: Resultsmentioning
confidence: 99%
“…First parity sows have a higher chance of suffering from bad reproductive performance in their next cycle [29], and therefore the effect of peforelin treatment on this animal category could have a greater impact on subsequent litter quality and reproductive parameters. Older sows on the otherhand, may suffer from lower reproductive performance, since this is the major cause of culling at higher parities [7, 9]. From a practical point of view, peforelin treatment of specific subcategories of sows within a high productive sow farms could be advised throughout the year for optimization of reproductive performance.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of a larger study, of which the main objective was to demonstrate differences in estrus rate between the treatment groups [17]. Statistical sample size calculations were performed in relation to this main objective.…”
Section: Methodsmentioning
confidence: 99%
“…Products, which have l-GnRH-III (peforelin) as the active substance, are marketed for the induction of estrus in sows after weaning and in sexually mature gilts after progestagen therapy. Different studies conducted in Germany and Belgium have confirmed that treatment with peforelin has positive effects on estrus induction in gilts and sows [15–17]. …”
Section: Introductionmentioning
confidence: 99%